2000
DOI: 10.1021/ar970172+
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to accelerate the hydrolysis of glycosidic bonds by factors approaching 10(17)-fold, glycosidases have evolved finely tuned active sites optimally configured for transition-state stabilization. Structural analyses of various enzyme complexes representing stable intermediates along the reaction coordinate, in conjunction with detailed mechanistic studies on wild-type and mutant enzymes, have delineated the contributions of nucleophilic and general acid/base catalysis, as well as the roles of noncovalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
482
1
6

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(508 citation statements)
references
References 52 publications
(114 reference statements)
19
482
1
6
Order By: Relevance
“…In addition to the nucleophilic attack on the anomeric carbon, this charged residue is also responsible for maintaining the correct ionization state of the acid-base residue (37). In several retaining glycoside hydrolases, the nucleophilic residue was also shown to assist in the oxocarbenium ion-like transition state stabilization by creating a very strong hydrogen bond with the sugar 2-hydroxyl (38,39). Replacement of the nucleophilic glutamic acid residue with the shorter aspartic acid can lead to reduction of about 10 3 -fold in the enzymatic activity (40 -42).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the nucleophilic attack on the anomeric carbon, this charged residue is also responsible for maintaining the correct ionization state of the acid-base residue (37). In several retaining glycoside hydrolases, the nucleophilic residue was also shown to assist in the oxocarbenium ion-like transition state stabilization by creating a very strong hydrogen bond with the sugar 2-hydroxyl (38,39). Replacement of the nucleophilic glutamic acid residue with the shorter aspartic acid can lead to reduction of about 10 3 -fold in the enzymatic activity (40 -42).…”
Section: Resultsmentioning
confidence: 99%
“…Such a focus of productive mutations upon improving transition state interactions with the C2-hydroxyl group is perhaps unsurprising because our earlier studies regarding this and other ␤-glucosidases have shown that interactions at the 2-position can contribute up to 10 kcal/mol to transition state binding (41,(43)(44)(45). Furthermore, structural studies on several of these enzymes had revealed that the most important contribution to such interactions was in fact the carbonyl oxygen of the nucleophile (45)(46)(47). Creation of the glycosynthase by mutation of Glu-358 thereby not only removes the ability to form a glycosyl-enzyme intermediate, but also removes a key stabilizing interaction to the substrate C2-hydroxyl group.…”
Section: Discussionmentioning
confidence: 99%
“…The existing structural and kinetic evidence for both classes of inverting enzymes supports a direct displacement mechanism involving an S N 2-like attack facilitated by an active site general base catalyst. Reactions catalyzed by retaining glycosidases are known to proceed via a double displacement mechanism involving the formation and subsequent breakdown of a covalent glycosyl-enzyme intermediate (16). Recent findings have, however, brought into question the applicability of this mechanism to retaining nucleoside diphosphate-utilizing glycosyltransferases since good candidates for the catalytic nucleophile are generally lacking, and in no case has an intermediate been trapped and characterized.…”
mentioning
confidence: 99%